2020
DOI: 10.1177/2309499019895650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sedation anesthesia on kinesiophobia and early outcomes after total knee arthroplasty

Abstract: Background: Total knee arthroplasty (TKA) operation is an effective treatment method in severe osteoarthritis worldwide. However, the number of patients with chronic pain and functional limitations in the postoperative period will continue to increase. Kinesiphobia is an important factor that affects the functional outcomes postoperatively. The aim of this study is to investigate the effects of intraoperative consciousness of the patients during surgery on kinesiophobia development and early functional outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 31 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…The results of the Cochrane Risk of Bias tool is shown in Table 3. Degirmenci et al [31], Monticone et al [6] and Cai et al [32] demonstrated low risk of bias, whereas Russo et al [33] failed to describe how their data were analysed, and whether if it was in accordance with pre-specified analysis plans.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the Cochrane Risk of Bias tool is shown in Table 3. Degirmenci et al [31], Monticone et al [6] and Cai et al [32] demonstrated low risk of bias, whereas Russo et al [33] failed to describe how their data were analysed, and whether if it was in accordance with pre-specified analysis plans.…”
Section: Search Resultsmentioning
confidence: 99%
“…Russo et al [33] did not specify the gender split and Body Mass Index (BMI) in their study but stated that the two groups were homogenous in terms of pre-operative age, gender, functional and psychological scores. Degirmenci et al [31] did not specify the mean BMI, but stated BMI over 40 in the exclusion criteria. Of 12 studies, 34.9% (380 of 1,089) were men.…”
Section: Study Design and Demographicsmentioning
confidence: 99%
See 3 more Smart Citations